Eliza : the story of Elizabeth Schuyler Hamilton - McNamara, Margaret (Schwartz & Wade Books, 2018)
Presents the life of Eliza Hamilton, wife of founding father Alexander Hamilton, covering her early years in New York, her married life with Alexander, and her later years as a generous philanthropist.